The need for and development of an adaptive listening and communication enhancement (LACE) program. - Sweetow RW; Sabes JH (Journal of the American Academy of Audiology, 2006)
Auditory training has long been advocated to enhance communication but has never been time or cost-effective. This article describes the concepts underlying the development of a home-based, interactive adaptive computer program designed to engage the adult hearing-impaired listener in the hearing-aid-fitting process, provide listening strategies, build confidence, and address cognitive changes characteristic of the aging process. An investigation using a between-group, within-subject design with pre- and post-test objective and subjective measures was conducted at five clinical sites. Sixty-five subjects were randomly placed into two groups, one receiving LACE (Listening and Communication Enhancement) immediately following baseline testing and one serving as a control for one month and then receiving training as a crossover group. Results showed statistically significant improvements for the trained subjects on all but one of the outcome measures. Barriers facing the widespread implementation of home-based aural rehabilitation are discussed.